Pengaruh kualitas produk dan positioning terhadap keputusan pembelian melalui kepercayaan merek produk asuransi kesehatan kumpulan di PT. Asuransi jiwa generali Indonesia regional Sumatera - Rahma Yulita (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to analyze empirically the effect of product quality and positioning on purchasing decisions through brand trust in the group health insurance PT. Generali Indonesia Sumatra Regional Life Insurance. This research uses a quantitative approach with survey methods and path analysis techniques. Data were collected from 81 companies participating in group health insurance with the number of employees above (>) 50 people, as a sample. The results showed; Product quality has a positive and significant effect on brand trust, positioning has a positive and significant effect on brand trust, brand trust has a positive and significant effect on purchasing decisions Product quality has a positive and significant effect on purchasing decisions through brand trust and positioning has a positive and significant effect on purchasing decisions through brand trust.